Examining the management of strategic resources in projects - Alhanshi, Moosa Ali Mas’oud (2019)
The resource-based theory theme concerns the exploitation of resources at organization level. However, the utilization of resources can be realized by the unique exploitation of those resources at the level of individual projects, supported by specific organizational dynamic and project capabilities in an innovative environment. In addition, project management as an application of knowledge and skills is a resource that can be utilized and could be a source of competitive advantage. This thesis seeks to explore how organizations might improve their performance and sustain their business by managing effectively their strategic resources at project level. The main underlying theory used in this thesis is the resource-based theory. Strategic resources are identified by four main characteristics. A strategic resource should be: valuable, rare, inimitable and should be supported by the organization Accordingly, the thesis aims to explore the possibility of applying the resource-based theory at project level. The methodology involved the use of both qualitative research, using semi-structured interviews and focus groups, and quantitative technique, using questionnaires. The data were all collected from petroleum industry organizations based in United Arab Emirates and Oman; petroleum industry (Projects team/department) and were analyzed using interpretations of the interview extracts and statistical questionnaires. The results show that at project level, the valuable and organizational support characteristics of strategic resources are valid and positively related to competitive advantage, both being affected by dynamic capabilities and innovative environment, while the rareness and inimitability characteristics showed less evolution. The results suggest a trend of replacing these with two other characteristics, namely unique exploitation and timely availability of resources. In addition, the results show a positive relationship between strategic resources and organizational/project performance. Finally, the thesis proposes a framework for the project-based resource characteristics which is expected to increase project success and become a source of competitive advantage for an organization. The possibility of generalizing the outcome to projects in other industry sectors and countries is also discussed. The implication of the findings is that, for organizations at project level, the main characteristics of strategic resources are that they are valuable, organizationally supported, can be uniquely exploited and are readily available. Those characteristics are better achieved in projects depending on two main factors: the dynamic capabilities of the organization and projects, and an innovative environment. Having strategic resources with these accompanying factors impacts the success of projects and, accordingly, organizational performance and its sustainability.
HydraID: hull:17717 Hydra Discover Access Group: public ETD Collection: ETDBusinessSchool
Keywords: Business